Dichotic listening deficits in amblyaudia are characterized by aberrant neural oscillations in auditory cortex. Issue 9 (September 2021) - Momtaz, Sara; Moncrieff, Deborah; Bidelman, Gavin M.
Highlights: Amblyaudia is characterized by a stark interaural asymmetry in dichotic listening performance. Stronger phase-locked β/γ oscillations within the bilateral auditory cortex for stimuli presented to the right ear in amblyaudia. Weaker functional connectivity in amblyaudia from right to left auditory cortex, despite overall stronger neural responses. Abstract: Objective: Children diagnosed with auditory processing disorder (APD) show deficits in processing complex sounds that are associated with difficulties in higher-order language, learning, cognitive, and communicative functions. Amblyaudia (AMB) is a subcategory of APD characterized by abnormally large ear asymmetries in dichotic listening tasks. Methods: Here, we examined frequency-specific neural oscillations and functional connectivity via high-density electroencephalography (EEG) in children with and without AMB during passive listening of nonspeech stimuli. Results: Time-frequency maps of these "brain rhythms" revealed stronger phase-locked beta-gamma ( 35 Hz) oscillations in AMB participants within bilateral auditory cortex for sounds presented to the right ear, suggesting a hypersynchronization and imbalance of auditory neural activity. Brain-behavior correlations revealed neural asymmetries in cortical responses predicted the larger than normal right-ear advantage seen in participants with AMB. Additionally, we found weaker functional connectivity in the AMB group from right to left auditory cortex, despite their stronger neural responses overall. Conclusion: Our results reveal abnormally large auditory sensory encoding and an imbalance in communication between cerebral hemispheres (ipsi- to -contralateral signaling) in AMB. Significance: These neurophysiological changes might lead to the functionally poorer behavioral capacity to integrate information between the two ears in children with AMB.